PROGRAM PENGUATAN BUDAYA ORGANISASI ISLAMI PADA UNIT KEGIATAN MAHASISWA (UKM) PRAMUKA UNIVERSITAS MUHAMMADIYAH SURAKARTA - Arqy Ahmadi, Mirzam (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
Organizational culture is a tool to unite various traits and characters in an organization which will become the identity of the organization. Organizational culture is very important to implement in an organization, both for employees and students. Various studies show that change management and organizational culture play an important role in creating good employee performance in an organization. This must be applied to organizations to support the smooth running and development of the organization, not only organizations and employees but also student organizations. The community service program through the capacity strengthening program (PPK) scheme is carried out with the "brainstorming" stage, opening insights and developing knowledge about organizational culture. With this community service program, students gain knowledge and practice regarding organizational culture and are able to implement the knowledge gained into student activity units (UKM).